Potentially inappropriate prescribing in dementia: a state-of-the-art review since 2007 - Kirsty Bowman; Linda Clare (BMJ Open)
Objectives Dementia frequently occurs alongside comorbidities. Coexisting conditions are often managed with multiple medications, leading to increased risk of potentially inappropriate medication and adverse drug reactions. We aimed to estimate prevalence of, and identify factors reported to be associated with, potentially inappropriate prescribing (PIP) for older individuals diagnosed with dementia.Design We used a state-of-the-art review approach, selecting papers written in English and published from 2007 to January 2018. Publications were retrieved from Scopus and Web of Science databases. Inclusion criteria included a formal diagnosis of dementia, a formal classification of PIP and reported prevalence of PIP as an outcome. Random effects models were used to provide a pooled estimate of prevalence of PIP. The Appraisal tool for Cross-Sectional Studies (AXIS tool) was used to assess bias in the included studies.Results The bibliographic search yielded 221 citations, with 12 studies meeting the inclusion criteria. The estimates of PIP prevalence for people living with dementia ranged from 14% to 64%. Prevalence was 31% (95% CI 9 to 52) in the community, and 42% (95% CI 30 to 55) in nursing/care homes. PIP included prescribing likely related to dementia (eg, hypnotics and sedative and cholinesterase inhibitors) and prescribing related to treatment of comorbidities (eg, cardiovascular drugs and non-steroidal anti-inflammatory medication). Higher levels of comorbidity were associated with increased risk of PIP; however, only one study investigated associations with specific comorbidities of dementia.Conclusion PIP remains a significant issue in healthcare management for people living with dementia. Higher levels of comorbidity are associated with increased prevalence of PIP, but the specific conditions driving this increase remain unknown. Further work is necessary to investigate PIP related to the presence of common comorbidities in patients living with dementia.